Orang Asli : isu, transformasi, dan cabaran - Gill, Sarjit S.; Ma'rof Redzuan (Penerbit Universiti Putra Malaysia, 2008)
Issues on Orang Asli, the indigenous peoples, and their socioeconomic conditions in Malaysia